Valuation of river restoration measures – Do residential preferences depend on leisure behaviour?. Issue 3 (4th March 2021) - Symmank, Lars; Profeta, Adriano; Niens, Christine
ABSTRACT: The number of river restoration projects grew steadily in recent years. However, freshwater ecosystems attract diverse stakeholder groups and thus are frequently a source of conflicting interests. A growing number of studies analyses stakeholder preferences towards river restoration projects albeit without distinguishing between them. However, a differentiated analysis is highly important, since public participation in decision-making is often restricted to a limited number of stakeholder groups. We used a discrete choice experiment to unravel preference heterogeneity of local residents towards river restoration depending on individual leisure behaviour. Our results show that some user groups have contrasting preferences to the vast majority of users. This is of particular interest, as these well-organized and influencing groups are considerably small and do not represent the general opinion of residents. Our results illustrate the large challenges for decision-makers and planners who are obliged to ensure public participation in river restoration projects.